Formation of skills to calculate the volumes of geometric bodies - Toleuhanova, R.Zh.; Shulgina-Tarachshuk, A.S.; Ardasheva, M.V.; Polupan, K.L. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The article is devoted to the formation of students' skills in calculating the volumes of geometric bodies. An effective reception of students' educational work at the final stage of solving the problem is proposed. In addition, the authors offer to familiarize themselves with the learning of the solution of the same problem in various ways, which helps students to move to a higher level in solving problems, choosing the most effective way to solve the problem. Authors analyzed the works of domestic and foreign researchers on the methods of learning activities that help students to better learn the material, systematize knowledge, help in solving problems. One of the main points to which special attention is paid is the training of students to study independently and creatively in order to include them in specially organized activities on the basis of sounded educational activities. The article also identifies the role of the student and the teacher in the process of performing independent work. An algorithm for drawing up a plan for solving problems is shown. It is noted that most of the methods of learning activity form the necessary skills. They help students to learn the material better, systematize knowledge, help in solving problems.
Геометриялық денелердің көлемін есептеуде біліктіліктерді қалыптастыру
Формирование умений по вычислению объёмов геометрических тел
Keywords: сalculation; task; solution; algorithm; method; equation; knowledge; solution structure of the problem; level; organize